2008
DOI: 10.1051/0004-6361:20077306
|View full text |Cite
|
Sign up to set email alerts
|

Integral field spectroscopy of four lensed quasars: analysis of their neighborhood and evidence for microlensing

Abstract: Context. Gravitationally lensed quasars constitute an independent tool to derive the Hubble constant through the time-delays of their different images; they offer as well the opportunity to study the mass distribution and interstellar medium of their lensing galaxies and, through microlensing due to stars in their lensing galaxy, they also allow one to study details of the emitting source. Aims. For such studies, one needs to have an excellent knowledge of the close environment of the lensed images in order to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 51 publications
0
31
1
Order By: Relevance
“…15 (Wisotzki et al 1999;Anguita et al 2008), similar to the well-known Cloverleaf quasar (Magain et al 1988). It is lensed by two galaxies at almost identical redshift (z G1 = 0.523 ± 0.001, z G2 = 0.526 ± 0.002; Eigenbrod et al 2006).…”
Section: Previous Resultsmentioning
confidence: 96%
“…15 (Wisotzki et al 1999;Anguita et al 2008), similar to the well-known Cloverleaf quasar (Magain et al 1988). It is lensed by two galaxies at almost identical redshift (z G1 = 0.523 ± 0.001, z G2 = 0.526 ± 0.002; Eigenbrod et al 2006).…”
Section: Previous Resultsmentioning
confidence: 96%
“…This is not a complete list of known microlensed quasars (see e.g. Richards et al 2004;Anguita et al 2008a), but these systems were among the first quasars lensed by a single lensing galaxy where significant microlensing of the BLR has been unveiled and discussed, with the advantage that the fully processed shows the extracted spectra of the lensed QSO images and of the lensing galaxy derived from the deconvolution. The last three panels f-h) show the calibrated spectra of these components following the procedure explained in Sect.…”
Section: The Extended Samplementioning
confidence: 99%
“…2 FWHM). Details on the observations and reductions are given in Anguita et al (2008a). For this data set, it was not possible to separate the spectra of images A and B of H1413+117.…”
Section: Data Collectionmentioning
confidence: 99%
“…In particular, Angonin et al (1990) found that the equivalent width of the emission lines is systematically smaller in component D than observed in the other components, a result which can be interpreted by microlensing of the continuum source, the larger region at the origin of the emission lines being unaffected. This effect, which appeared to last at least a decade (Chae et al 2001;Anguita et al 2008a), offers the possibility to separate the microlensed attenuated continuum (i.e. the absorption profile) from the true emission line profile, thus providing new clues to the formation of BAL profiles (Hutsemékers 1993;Hutsemékers et al 1994).…”
Section: Introductionmentioning
confidence: 99%